(untitled) (TEST Antologia di Diritto Pubblico, 2023)
Antologia di Diritto Pubblico (ADP) (ISSN 2975-2191) is a biannual journal promoted by the Faculty of Law of the University of Trento and the Department of Economics and Business Studies of the UPO - Università del Piemonte Orientale. The journal offers insight into some relevant topics for the study of public law, also with a critical approach, building on the analysis of some of the classical texts of this discipline.